Bibliometric Analysis: Research on Batik in International Publications - Denny Sukma Eka Atmaja; Herianto; Muhammad Kusumawan Herliansyah; Andi Sudiarso (School of Industrial and System Engineering, Telkom University, 2023)
Batik is an Indonesian cultural tradition that carries profound philosophical meanings embedded inits patterns and high artistic value. This is evident from its early origins when batik was used withina very limited keraton environment. Now it has become a commodity of the Indonesian creativeindustry that has ventured into the global market. This paper addresses the following issues: the annualnumber of international scholarly publications in the field of batik to be published in Scopus, theproductivity of researchers working in the field of batik, and the methodology for using keywords tomap the development of international research publications on batik. Based on the discussion andsimulation using VOSviewer software, it can be concluded that the development and growth,especially in the field of batik, from 2012 – 2022, indexed in Scopus, reached 213 publications(18.73%) in 2020. The majority of publications in the field of batik were published in the IOPConference Series: Earth and Environmental Science. Diponegoro University is the institution thathas published the most research in the field of batik, and Indonesia is one of the countries with thehighest contributors. The researcher with high productivity in the field of batik is Widiaty, I, with atotal of 15 publications from 2012 to 2022, specifically in the field of batik. Regarding thedevelopment map of the field of batik based on co-word analysis, there are 7 clusters, where newresearch topics are identified that can still be further developed, especially in the field of batik